Efficacy of the Mendelsohn maneuver combined with repetitive facilitation principles in poststroke dysphagia - Wenjing Jia; Caihong Cui; Liang Qin; Jialin Sun; Chunxiao Wan (Medicine, 2026)
Background: This study aimed to evaluate the effects of Mendelsohn maneuver training combined with repetitive facilitation principles on swallowing function in patients with poststroke dysphagia. Methods: This prospective, assessor-blinded randomized controlled trial assessed 60 patients for eligibility and randomly assigned 56 eligible participants to a control or experimental group. The control group received conventional indirect swallowing therapy, whereas the experimental group received the Mendelsohn maneuver combined with repetitive facilitation principles. Treatment duration and therapist contact were matched between groups. Training was delivered for 20 minutes per session, 5 times weekly, for 4 weeks. Outcomes included the Penetration–Aspiration Scale, pharyngeal residue, upper esophageal sphincter opening diameter, Dysphagia Outcome and Severity Scale, and nasogastric tube removal. Results: All 56 randomized participants completed treatment and posttreatment assessment. Both groups showed improvement in swallowing function. Compared with the control group, the experimental group had lower Penetration–Aspiration Scale scores at Day 28 and greater improvement in Dysphagia Outcome and Severity Scale scores. Findings for pharyngeal residue were inconsistent and should be considered exploratory: vallecular residue change favored the experimental group, whereas posttreatment scores did not differ, and no significant difference was found in pyriform sinus residue change. No significant group differences were observed in upper esophageal sphincter opening improvement or nasogastric tube removal. Conclusion: The combined intervention may provide additional benefits for swallowing safety and overall swallowing function in patients with poststroke dysphagia.